Organisational Responses to Thailand’s Economic Crisis: Analyzing Construction Companies - Bettina Buechel (Asian Academy of Management Journal, 1998)
Organisational Responses to Thailand’s Economic Crisis: Analyzing Construction Companies (PDF not available